Confluent and reticulated Gougerot–Carteaud papillomatosis: diagnostic criteria; efficacy of azithromycin - N. Yu. Burtseva; G. N. Mikheev; K. N. Monakhov; E. V. Sokolovskiy (Лечащий Врач)
A review of the literature on the etiology, pathogenesis and clinical manifestations of papillomatosis confluent and reticulated Gougerot–Carteaud (PCR) is presented. The diagnostic criteria and differential diagnosis of PCR are discussed. A 36-year-old man with obesity grade 2 and typical manifestations of PCR is described. The treatment with azithromycin during 6 days appeared to be sufficient to decrease the rash which had existed for 7 years.